Biopsychosocial determinants of cortisol levels in cervical cancer patients: the roles of spirituality, anxiety, and depression undergoing chemotherapy: Determinantes biopsicosociales de los niveles de cortisol en pacientes con cáncer de cuello uterino: el papel de la espiritualidad, la ansiedad y la depresión durante el tratamiento con quimioterapia - Listanto, Virgiawan; Tahir, Mardiah; Syahrul; Asni, St. Nur; Arifuddin, Sharvianty; Previana, Rina (Gaceta Médica de Caracas, 2026)
Introduction: In patients with cancer, spirituality plays a central role in coping with the emotional, psychological, and existential burdens associated with the disease. Objectives: This study aimed to examine the relationships between spiritual well-being and psychological outcomes, specifically anxiety and depression, as well as serum cortisol levels, as physiological stress markers, in cervical cancer patients undergoing chemotherapy. Methods: Employing a cross-sectional observational design, we included patients diagnosed with advanced-stage cervical cancer at a tertiary referral hospital, Dr. Wahidin Sudirohusodo General Teaching Hospital in Makassar, Indonesia. Data were assessed using validated instruments, i.e, the Zung Self-rating Anxiety Scale (SAS), the Zung Self-rating Depression Scale (SDS), the Daily Spiritual Experience Scale (DSES), and laboratory measurements of serum cortisol levels.